2020
DOI: 10.1108/jmp-09-2019-0538
|View full text |Cite
|
Sign up to set email alerts
|

Workspace transitions: conceptualizing and measuring person–space fit and examining its role in workplace outcomes and social network activity

Abstract: PurposeAlthough the physical environment provides an important context for employees' work, there remain divergent findings regarding how different spatial settings, such as more open or more closed workspaces, impact employees. Employing research on the functions of the physical work environment, we contribute to a growing body of research on employees' interactions with their workspace by developing and measuring the notion of person–space fit (P-S fit). This construct affords examination of the multi-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This work contributes in several ways to the literature on open offices, which heretofore has not been explicitly examined from a job crafting perspective. Our study is suggestive of specific purposeful efforts to job craft to improve person–space fit in open offices to counter negative effects discussed in open office research, including reduced face‐to‐face communication and decreased likelihood of forming new social ties (Bankins et al, 2021; Bernstein & Turban, 2018). Also, this work provides numerous examples of how person–environment fit (Hoendervanger et al, 2019) can be improved in open office settings through job crafting via barriers (such as the use of imaginary physical barriers) as well as via bridges (signaling artifacts, such as a round table to encourage group problem solving).…”
Section: Discussionmentioning
confidence: 58%
“…This work contributes in several ways to the literature on open offices, which heretofore has not been explicitly examined from a job crafting perspective. Our study is suggestive of specific purposeful efforts to job craft to improve person–space fit in open offices to counter negative effects discussed in open office research, including reduced face‐to‐face communication and decreased likelihood of forming new social ties (Bankins et al, 2021; Bernstein & Turban, 2018). Also, this work provides numerous examples of how person–environment fit (Hoendervanger et al, 2019) can be improved in open office settings through job crafting via barriers (such as the use of imaginary physical barriers) as well as via bridges (signaling artifacts, such as a round table to encourage group problem solving).…”
Section: Discussionmentioning
confidence: 58%
“…collaboration is easier within accessible, open spaces (Zamani and Gum, 2019). Supporting this reasoning, within a working sample, a greater level of fit in a new office promoted higher performance (Bankins et al, 2021), while Hoendervanger et al (2019) found that TE fit promoted performance on a cognitive task within a population of students in virtual reality simulations. Soriano et al (2021) reported that office type-work pattern fit contribute to in-role performance indirectly via flow experience.…”
Section: Hypotheses For Supplementary Examinationsmentioning
confidence: 93%